Ativismo e comportamento do consumidor vegano - Silva, Mayara Mota da (2018)
Veganism has emerged as a diet proposal within vegetarianism. Today however far beyond a diet proposal, veganism is considered by many of its adherents as a lifestyle guided by moral precepts. The activism incorporated into the vegan positioning which corresponds to a kind of anti-consumption according to the classification proposed by Iyer and Muncy (2009) has been highlighted in several actions realized in favor of the animal cause and more engaged position in relation responsible consumption. Based on the proposal of Stern et al. (1999) on activism the research realized had the objective of analyzing the connection between activism and vegan consumer behavior. For this a bibliographical research about the topic was made where, through it was possible to elaborate a questionnaire that would enable the study in question. The questionnaire was applied to an agro-ecological fair in the city of Fortaleza and through a group of social network veganism totaling 121 respondents. The descriptive research was characterized by a quantitative perspective where the results pointed out the position of majority of supporters within the vegan activism and revealed the close connection between the vegans and anti-consumer characteristics.